الممسوخون في القرآن الكريم: صفاتهم والعبر من قصصهم - Syed Omar, Syed Mohd Hafiz (2011)
This article aims to gather and analyze the conflicting interpretations given by the theologians on issues related to al-Maskhu. The researcher will try to elaborate various interpretations given in defining the meaning of al-Maskhu and then choose the strongest one. The researcher will also identify the character of the Mamsukhun as been described by the Quran and explain the lessons obtained from it. This research will utilize the documentary analysis method. At the end, it is concluded that the meaning of al-Maskhu in the Quran is the real evolution and not the metaphor one. As for the curse that befell on ashab al-Sabt, it is concluded that it is the combination of al-Maskhu and avoidance from Allah blessing. This is because al-Maskhu itself is the biggest temperance from Allah blessing. As for those who obey Allah, they will be kept away from Allah’s wrath.